Looking age-appropriate while growing old gracefully: A qualitative study of ageing and body image among older adults. (April 2016) - Jankowski, Glen S; Diedrichs, Phillippa C; Williamson, Heidi; Christopher, Gary; Harcourt, Diana
Body dissatisfaction can be significantly detrimental to wellbeing. Little is known about older adults' body image, despite the fact that ageing causes unique bodily changes and that sociocultural pressures to resist these changes abound. We conducted six focus groups with a UK community sample of White British and South Asian older adults aged 65–92 years. Thematic analysis highlighted four themes: appearance indicates capability and identity; physical ability trumps appearance; felt pressures to age 'gracefully' while resisting appearance changes; and gender and cultural differences. These findings suggest that older adults' body image can have important implications for their wellbeing and merits researchers' attention.